2009
DOI: 10.1007/s10562-009-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Cobalt Containing MCM-41 and HMS in Liquid Phase Oxidation of Diphenylmethane

Abstract: Cobalt containing MCM-41 and HMS were synthesized by direct hydrothermal (DHT) and post synthesis methods (grafting and immobilization). The catalytic activity of these materials was investigated in the liquid phase oxidation of diphenylmethane at 80°C with TBHP (70 wt%) as oxidant. Comparative study of cobalt containing MCM-41 and HMS was carried out to reveal the catalytic performance of framework, extraframework and immobilized cobalt species. The role of the solvent in the performance of catalyst was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Interestingly the reaction proceeded in a remarkable manner by using the siliceous either MCM-41 or MCM-48 with a substrate conversion of > 80 % within 15 min of reaction and selective towards 2-methoxybenzoquinone (Table-2, entry 2). Recently, we have observed that mesoporous silicas can catalyse the reaction yielding selectively methoxybenzoquinone [20]. Further we have observed that apocynol (1) is susceptible to oxidation in presence of H 2 O 2 alone and the reaction proceeds in an uncontrolled and non-selective manner resulting in several high molecular weight products (not identified).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly the reaction proceeded in a remarkable manner by using the siliceous either MCM-41 or MCM-48 with a substrate conversion of > 80 % within 15 min of reaction and selective towards 2-methoxybenzoquinone (Table-2, entry 2). Recently, we have observed that mesoporous silicas can catalyse the reaction yielding selectively methoxybenzoquinone [20]. Further we have observed that apocynol (1) is susceptible to oxidation in presence of H 2 O 2 alone and the reaction proceeds in an uncontrolled and non-selective manner resulting in several high molecular weight products (not identified).…”
Section: Methodsmentioning
confidence: 99%
“…It is quite understandable that hydrogen peroxide can be activated either by cobalt [20] or silanol groups [44] 41 containing silanol groups as well as Co(II) yields mixture of products 2 and 3. Increment of OH-groups with increase in cobalt content in CoMCM-41 can lead to proton extraction both from benzylic carbon as well as from phenolic substrate.…”
Section: Catalyst Ch Cn H Omentioning
confidence: 99%
See 1 more Smart Citation
“…1 As a consequence, for the past decade much efforts have been made to develop more economic and clean processes for the synthesis of aromatic ketones by the oxidation of aromatics over a variety of heterogeneous catalysts. Up to now, the majority of studies reported the oxidation of diphenylmethane to benzophenone [2][3][4][5][6][7][8][9][10][11][12] and ethylbenzene to acetophenone. [3][4][5][6][12][13][14][15][16][17][18][19] Other aromatics like 4-nitroethylbenzene 3,6 and fluorene 12,[20][21][22] have received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…MCMs type materials possess characteristic mesoporous structure, large surface area, and high thermal stability, which allow their potential applications in catalysis, adsorbants, and energy conversion. 23,24 Recently, M-MCM-41 (M = Ti, V, Cr), 5 cobalt containing MCM-41, 8,11 Mn-MCM-41, 10,18,19 and Cr-MCM-41 12,13 were prepared and applied to the liquid-phase oxidation of diphenylmethane, ethylbenzene, or 4-nitroethylbenzene with low to moderate catalytic activities. Although vanadium-containing MCM-41 materials have been applied to the oxidation of light alkanes, 25 benzene, 26,27 and styrene, 27 only few studies have been reported for other aromatics so far.…”
Section: Introductionmentioning
confidence: 99%